The clinical and genomic epidemiology of seasonal human coronaviruses in congregate homeless shelter settings: A repeated cross-sectional study - Eric J. Chow; Amanda M. Casto; Julia H. Rogers; Pavitra Roychoudhury; Peter D. Han; Hong Xie; Margaret G. Mills; Tien V. Nguyen; Brian Pfau; Sarah N. Cox; Caitlin R. Wolf; James P. Hughes; et al. (Elsevier, 2022)
Summary: Background: The circulation of respiratory viruses poses a significant health risk among those residing in congregate settings. Data are limited on seasonal human coronavirus (HCoV) infections in homeless shelter settings. Methods: We analysed data from a clinical trial and SARS-CoV-2 surveillance study at 23 homeless shelter sites in King County, Washington between October 2019-May 2021. Eligible participants were shelter residents aged ≥3 months with acute respiratory illness. We collected enrolment data and nasal samples for respiratory virus testing using multiplex RT-PCR platform including HCoV. Beginning April 1, 2020, eligibility expanded to shelter residents and staff regardless of symptoms. HCoV species was determined by RT-PCR with species-specific primers, OpenArray assay or genomic sequencing for samples with an OpenArray relative cycle threshold <22. Findings: Of the 14,464 samples from 3281 participants between October 2019-May 2021, 107 were positive for HCoV from 90 participants (median age 40 years, range: 0·9-81 years, 38% female). HCoV-HKU1 was the most common species identified before and after community-wide mitigation. No HCoV-positive samples were identified between May 2020-December 2020. Adults aged ≥50 years had the highest detection of HCoV (11%) among virus-positive samples among all age-groups. Species and sequence data showed diversity between and within HCoV species over the study period. Interpretation: HCoV infections occurred in all congregate homeless shelter site age-groups with the greatest proportion among those aged ≥50 years. Species and sequencing data highlight the complexity of HCoV epidemiology within and between shelters sites. Funding: Gates Ventures, Centers for Disease Control and Prevention, National Institute of Health.